METHODOLOGICAL CONCEPTS OF BUILDING UP CREATIVITY TYPOLOGY - Bogoyavlenskaya, Diana; Kotlyarova, Liubov (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
The article traces the historical dynamics of the initial concepts of creativity. It is shown how the concepts of Russian methodology provided a principally new approach to studies of creativity psychology and building up the creativity typology. The original method of the Creative Field allows defining stimulus-productive, heuristic and creative types of the approaches to creativity. The conditions of carrying out the experiment using this method are described. Further the research results are given referring characteristics of the motivational profile in groups, defined according to the creativity typology.